Tindak Tutur Asertif dan Ekspresif pada Video Ekosistem Pendidikan Merdeka dalam Belajar - Intan Wulan Sari (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Speech is used by a speaker to convey purpose and purpose to the speech partner, through speech and the accompanying context. The goal of this time, therefore, is to identify a single act of assupportive and expressive speech in the appeal of najelaa shihab in a large youtube video entitled "free education ecosystem of learning." By using a qualitative methodological approach with qualitative descriptive and theoretical approaches with pragmatic studies of asmotivated and expressive monosyllable speech. Studies are conducted with several stages ranging from watching, transcribing, analyzing, classification, identifying, to deduction. The data discussed is the speech of najelaa shihab in the bukalyoutube channel entitled "free education ecosystem of learning," from beginning to end of the video. Research on this time has resulted in a total of 48 different ACTS of speech, with a composition of 30 active speech and 18 expressive speech. The details of such ACTS as: expressing views (10), pointing out (11), showing (7), and mentioning (2). Whereas the expressions found are: complain (2), criticize (6), blame (2), praise (1), and thank (1)